Pemberdayaan Guru Seni Budaya SMA Negeri 1 Harau Meningkatan Kualitas Pagelaran Seni dengan Rekayasa Ruang/Peralatan Audio Berstandar Akustik - Maestro, Esy; Sudarman, Yos; Gusnedi, Gusnedi (Universitas Negeri Padang, 2024)
Art performances in schools can be carried out as an intracurricular part of cultural arts learning. On the other hand, art performances are also a forum for student creativity in various multi-event extracurricular activities with various targets. Of the many art performances that have been performed by students of SMA Negeri 1 Harau, both in music, dance, theater, and so on, the results of the performances achieved also vary in quality. However, the discussion of the quality of the performance results is more concentrated on the material issues of music, dance, theater, and so on. Even though the problem of the absence of performance room arrangement and audio equipment systems that meet the acoustic standards of art performances, is also a determining factor for the quality or not of art performances in schools. The results of monitoring since the survey, it is suspected that teachers do not have knowledge and technical skills about this problem, so the burden of the risk of art performances that are of low audio and acoustic quality, and have damaged the performance material itself, ultimately falls on students and audio/soundsystem equipment providers. The implication is that the quality of art performances in schools is not comparable to the waste of school budgets that have been provided for the procurement of an art performance.